Evaluation of the Short‐, Mid‐, and Long‐Term Effects of Tofacitinib on Lymphocytes in Patients With Rheumatoid Arthritis - van Vollenhoven, Ronald (Arthritis Rheumatol, 2019)
OBJECTIVE: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Altered lymphocyte cell counts and a potential association with increased infection rates have been reported in RA patients treated with JAK inhibitors. This analysis was undertaken to evaluate the short‐, mid‐, and long‐term effects of tofacitinib on lymphocytes and infection rates in patients with RA. METHODS: In this post hoc analysis, absolute lymphocyte counts (ALCs) were obtained from phase III studies (12–24 months; n = 717–958) and phase I/II/III/long‐term extension studies of tofacitinib (≤117 months) (All RA population; n = 7,061); lymphocyte subset counts (LSCs) were from phase II studies (1.5–6 months’ exposure; n = 236–486), an ORAL Sequel vaccine substudy (~22 months; n = 198), and an ORAL Sequel lymphocyte substudy (~50 months; n = 55–1,035) of tofacitinib. The reversibility of ALC/LSC changes was evaluated. The relationship of ALC and LSC to infections was analyzed in the All RA population. The value of monitoring ALC alone was assessed by examining correlations between ALCs and LSCs. RESULTS: Tofacitinib treatment resulted in an initial increase in ALC versus pretreatment baseline, which gradually declined to steady state by ~48 months. CD4+ and CD8+ T cell counts decreased over long‐term treatment, and ALC and LSC changes were reversible upon treatment cessation. Patients with ALCs of <500 cells/mm(3) had an increased risk of serious infections. There was no strong association between CD4+ T cell, CD8+ T cell, B cell, or natural killer cell counts and serious infection incidence rates. ALC and CD4+ or CD8+ T cell counts correlated well (R = 0.65–0.86). CONCLUSION: Our findings indicate that monitoring of ALC alone appears to be adequate to assess infection risk in tofacitinib‐treated patients with RA.